The Natives Emigrating in the Cultural Community of Thailand from the Tourism Adaptation - Supoj Prompayuk; Panayu Chairatananonda (My University, 2018)
Cultural heritages communities in Thailand were mostly adapted into a tourist attraction. The objective of this study was to investigate the occurrences of the natives in the central region of Thailand emigrating from their aboriginal communities from this cause. Since This adaptation successfully generates more income to the community, it also attracts outsiders to come in and exploit the better economic situation but pushes the natives away. Thus, the uniqueness and attractiveness of the local way of life and culture starts to disappear and will lose them almost entirely, such as the occurrences at Amphawa, Samchuk and Chiang Khan community.
Keywords: Tourist attraction; Diverse Aspects of Tourism Research